Changing Democracy? Why Inertia is Winning Over Innovation. Issue 4 (1st October 2016) - Núñez, Lidia; Close, Caroline; Bedock, Camille
Abstract : There is a widespread belief that in order to cure the so-called crisis of democracy, citizens' involvement in decision-making processes needs to be fostered. However, despite the fact that there is a move towards more inclusive institutions in Europe, changes implementing democratic innovations at the national level remain rare. Why are democratic innovations not implemented more often? In this article, we provide explanations on why inertia seems to win over change through an analysis of party elites' willingness to enact democratic innovations across 15 European democracies, by using the PartiRep Comparative MP Survey. This research concentrates on party-level factors: party age, time in government and party ideology. Findings suggest that institutional inertia is partially rooted on the fact that party elites' support for democratic innovations is heavily related to anti-establishment parties, to left-wing parties and to parties with limited access to power.